2022
DOI: 10.1002/mrm.29215
|View full text |Cite
|
Sign up to set email alerts
|

Personalized local SAR prediction for parallel transmit neuroimaging at 7T from a single T1‐weighted dataset

Abstract: Parallel RF transmission (PTx) is one of the key technologies enabling high quality imaging at ultra-high fields (≥7T). Compliance with regulatory limits on the local specific absorption rate (SAR) typically involves over-conservative safety margins to account for intersubject variability, which negatively affect the utilization of ultra-high field MR. In this work, we present a method to generate a subject-specific body model from a single T1-weighted dataset for personalized local SAR prediction in PTx neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Some related DL approaches in UHF imaging have been recently reported for subject‐specific calibration of the transmit B1+$$ {\mathrm{B}}_1^{+} $$‐fields 25–29 . Abbasi‐Rad et al 28 predicted channel‐combined B1+$$ {\mathrm{B}}_1^{+} $$‐magnitudes from a standard localizer to determine a FA scaling factor for adiabatic RF pulses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some related DL approaches in UHF imaging have been recently reported for subject‐specific calibration of the transmit B1+$$ {\mathrm{B}}_1^{+} $$‐fields 25–29 . Abbasi‐Rad et al 28 predicted channel‐combined B1+$$ {\mathrm{B}}_1^{+} $$‐magnitudes from a standard localizer to determine a FA scaling factor for adiabatic RF pulses.…”
Section: Discussionmentioning
confidence: 99%
“…Some related DL approaches in UHF imaging have been recently reported for subject-specific calibration of the transmit B + 1 -fields. [25][26][27][28][29] Abbasi-Rad et al 28 predicted…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further to translational/rotational position of the body models, partial positional variations (i.e., position of the limbs relative to each other and to the body) can also have a profound effect on local SAR 67,68 . A recent study has demonstrated that using personalised SAR models can reduce the effect of the differences between the simulated models and the actual subject on SAR underestimation 69 . Such models would inherently be patient‐position aware and, therefore, can potentially be used to overcome positional variation‐related SAR underestimation, especially if the associated ~30‐min workflow for pTx observed in the initial implementation 69 can be reduced to clinically feasible times.…”
Section: Discussionmentioning
confidence: 99%